2009
DOI: 10.1007/s10265-009-0256-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression patterns in seed plant shoot meristems and leaves: homoplasy or homology?

Abstract: The fossil record reveals that seed plant leaves evolved from ancestral lateral branch systems. Over time, the lateral branch systems evolved to become determinate, planar and eventually laminar. Considering their evolutionary histories, it is instructive to compare the developmental genetics of shoot apical meristems (SAMs) and leaves in extant seed plants. Genetic experiments in model angiosperm species have assigned functions of meristem maintenance, specification of stem cell identity, boundary formation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 114 publications
4
67
0
Order By: Relevance
“…Classic and recent research has shown that compound leaf development requires prolonged activity of the MB during primary morphogenesis. Genetic and hormonal factors that regulate MB activity were shown to partially overlap with those regulating SAM activity, in accordance with the evolutionary origin of a leaf as a modified shoot Floyd and Bowman, 2010). The temporal and spatial length of the MB activity determines the extent of the indeterminate phase in leaf growth and the consequent level of leaf complexity (Hagemann and Gleissberg, 1996) (Fig.…”
Section: Role and Maintenance Of The Marginal Blastozonementioning
confidence: 65%
“…Classic and recent research has shown that compound leaf development requires prolonged activity of the MB during primary morphogenesis. Genetic and hormonal factors that regulate MB activity were shown to partially overlap with those regulating SAM activity, in accordance with the evolutionary origin of a leaf as a modified shoot Floyd and Bowman, 2010). The temporal and spatial length of the MB activity determines the extent of the indeterminate phase in leaf growth and the consequent level of leaf complexity (Hagemann and Gleissberg, 1996) (Fig.…”
Section: Role and Maintenance Of The Marginal Blastozonementioning
confidence: 65%
“…We speculate that this gene module is utilized in other examples of morphological variation -similar to the story of KNOX and CUC genes, and their roles in leaf diversity (Bharathan et al, 2002;Blein et al, 2008;Floyd and Bowman, 2010).…”
Section: The Role Of Lg1 and Wab1 In Plant Architecturementioning
confidence: 77%
“…The relationship between SFT/SP and LA remains to be determined, but the fact that loss of SP enhances the La-2 phenotype suggests that these factors might act in parallel or at successive stages of leaf development to terminate indeterminate growth. Whereas LA and SFT/SP promote maturation, KNOXI proteins have been shown to promote an extended PM stage in tomato and other species (Barth et al, 2009;Canales et al, 2010;Floyd and Bowman, 2010;Hay and Tsiantis, 2006;Janssen et al, 1998;Shani et al, 2009;Uchida et al, 2010). Alternatively, KNOXI proteins have been interpreted to act within the morphogenetic window to reiterate the basic leaf shape, rather than extend this window (Efroni et al, 2010;Hareven et al, 1996;Ori et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of leaf growth by LANCEOLATE CUC-like transcription factors and auxin have been shown to be involved in patterning morphogenetic events at the leaf margin in both simple and compound leaves (Barkoulas et al, 2008;Berger et al, 2009;Blein et al, 2010;Floyd and Bowman, 2010;Koenig et al, 2009;Nikovics et al, 2006). It thus appears that the timing of initiation of marginal structure with respect to the maturation schedule and the developmental stage of the leaf will determine the nature of these marginal structures.…”
Section: Research Articlementioning
confidence: 99%